The Natural History of Femoroacetabular Impingement - Kuhns, Benjamin D.; Weber, Alexander E.; Levy, David M.; Wuerz, Thomas H. (Frontiers in Surgery, 2015)
Femoroacetabular impingement (FAI) is a clinical syndrome resulting from abnormal hip joint morphology and is a common cause of hip pain in young adults. FAI has been posited as a precursor to hip osteoarthritis, however, conflicting evidence exists and the true natural history of the disease is unclear. The purpose of this article is to review the current understanding of how FAI damages the hip joint by highlighting its pathomechanics and etiology. We then review the current evidence relating FAI to osteoarthritis. Lastly, we will discuss the potential of hip preservation surgery to alter the natural history of FAI, reduce the risk of developing osteoarthritis and the need for future arthroplasty.